Inherited CD70 deficiency in humans reveals a critical role for the CD70–CD27 pathway in immunity to Epstein-Barr virus infection - Izawa, Kazushi; Martin, Emmanuel; Soudais, Claire; Bruneau, Julie; Boutboul, David; Rodriguez, Rémy; Lenoir, Christelle; Hislop, Andrew D.; Besson, Caroline; Touzot, Fabien; Picard, Capucine; Callebaut, Isabelle; et al. (The Journal of experimental medicine, 2017)
Epstein-Barr virus (EBV) infection in humans is a major trigger of malignant and nonmalignant B cell proliferations. CD27 is a co-stimulatory molecule of T cells, and inherited CD27 deficiency is characterized by high susceptibility to EBV infection, though the underlying pathological mechanisms have not yet been identified. In this study, we report a patient suffering from recurrent EBV-induced B cell proliferations including Hodgkin’s lymphoma because of a deficiency in CD70, the ligand of CD27. We show that EBV-specific T lymphocytes did not expand properly when stimulated with CD70-deficient EBV-infected B cells, whereas expression of CD70 in B cells restored expansion, indicating that CD70 on B cells but not on T cells is required for efficient proliferation of T cells. CD70 was found to be up-regulated on B cells when activated and during EBV infection. The proliferation of T cells triggered by CD70-expressing B cells was dependent on CD27 and CD3 on T cells. Importantly, CD27-deficient T cells failed to proliferate when stimulated with CD70-expressing B cells. Thus, the CD70–CD27 pathway appears to be a crucial component of EBV-specific T cell immunity and more generally for the immune surveillance of B cells and may be a target for immunotherapy of B cell malignancies.